Cancer vaccines: designing artificial synthetic long peptides to improve presentation of class I and class II T cell epitopes by dendritic cells. (3rd April 2019) - Rabu, Catherine; Rangan, Laurie; Florenceau, Laetitia; Fortun, Agnès; Charpentier, Maud; Dupré, Emilie; Paolini, Léa; Beauvillain, Céline; Dupel, Estelle; Latouche, Jean-Baptiste; Adotevi, Olivier; Labarrière, Nathalie; et al.
ABSTRACT: There is now a consensus that efficient peptide vaccination against cancer requires that peptides should (i) be exclusively presented by professional APC and (ii) stimulate both CD4 and CD8-specific T cell responses. To this aim, in recent trials, patients were vaccinated with pools of synthetic long peptides (SLP) (15–30 aa long) composed of a potential class I epitope(s) elongated at both ends with native antigen sequences to also provide a potential class II epitope(s). Using MELOE-1 as a model antigen, we present an alternative strategy consisting in linking selected class I and class II epitopes with an artificial cathepsin-sensitive linker to improve epitope processing and presentation by DC. We provide evidence that some linker sequences used in our artificial SLPs (aSLPs) could increase up to 100-fold the cross-presentation of class I epitopes to CD8-specific T cell clones when compared to cross-presentation of the corresponding native long peptide. Presentation of class II epitopes were only slightly increased. We confirmed this increased cross-presentation after in vitro stimulation of PBMC from healthy donors with aSLP and assessment of CD8-specific responses and also in vivo following aSLP vaccination of HLA*A0201/HLA-DRB0101 transgenic mice. Finally, we provide some evidence that vaccination with aSLP could inhibit the growth of transplanted tumors in mice. Our data thus support the use of such aSLPs in future cancer vaccination trials to improve anti-tumor CD8 T cell responses and therapeutic efficacy.